The Role of Governments in Developing MSMEs in Line with Social Changes Due to the Covid-19 Pandemic - Bakhtiar, Sofyan; Ramlan, Pratiwi; Saleh, Wahyuni; Andreani, Andi Riska; Herman, Bahtiar (KnE Social Sciences, 2022)
MSMEs are one of many industries that have been impacted by the Covid-19 pandemic that has swept the globe, particularly in Indonesia. Since the Covid-19 virus was declared a pandemic two years ago, MSMEs have seen a significant drop in turnover. In addition to MSMEs’ adaptation and creativity, the development of MSMEs undoubtedly necessitates government help to assist enterprises in surviving and competing in the contemporary era. The goal of this study was to look at the government’s role in establishing MSMEs in light of the COVID-19 pandemic’s socio-economic changes. Descriptive qualitative approaches were used, as well as data gathering techniques such as observation, interviewing, and documentation. According to the findings, the government has aided the development of MSMEs by, for example, providing assistance through people’s business loans, simplifying business permits, lowering the percentage of income taxes, and providing business assistance; however, during the pandemic, rules such as social distancing, activity restrictions, and operating hour restrictions have resulted in a decrease in MSME income. Providing support/intensive aid to MSMEs is still critical, and using technology as a digital marketing medium is a way to stay afloat in the face of societal changes that limit outside operations. Keywords: MSME, developing, social changes, Covid-19 pandemic